Effects of virgin coconut oil as adjunct therapy in the treatment of allergic rhinitis - Zainuddin, Nazli (2012)
Allergic rhinitis is a disease of type 1 immediate hypersensitivity reaction, which is characterized by one or more of the following symptoms: sneezing, rhinorrhea, nasal congestion and itchiness. Management of allergic rhinitis includes patient education and counselling, medications and allergen-specific immunotherapy. In this study, we were determining-the effects of virgin coconut oil as adjunct therapy in the treatment of allergic rhinitis. To compare magnitude of allergic rhinitis symptoms (nasal and non nasal symptoms) in allergic rhinitis improvement after virgin coconut oil ingestion and to determine the side effects of virgin coconut oil following its consumption.An open label prospective randomised controlled clinical trial was carried out in Otorhinolaryngology clinic HUSM. Fifty-two patients with history suggestive of allergic rhinitis were recruited in this study. They were divided into control and test group. The patient's particular and history takings were recorded and compiled. Patients then undergone skin prick test. The allergens included in this study were Derrnatophagoides pteronyssinus (house dust mite), Dermatophagoides farina (house dust mite), Blomia tropicalis (house dust mite), Felis domesticus (cat) and shrimp. Symptoms score were recorded at before and after completed 28 days of study. The control group was given oral antihistamine while the test group was given oral antihistamine and 10 ml ofvirgin coconut oil three times per day. The highest prevalence of positive skin prick test among subjects in control group was Dermatophagoides pteronyssinus ( 100%) and the lowest prevalence was Dermatophagoides faririae (11.5% ). The highest prevalence of positive skin prick test among subjects in test group was Dermatophagoides pteronyssinus (96.2%) and the lowest prevalence was Felis domesticus (42.3%). There were no statistically significance differences in the mean nasal and non-nasal symptom score between test and control group, except for the mean nasal sneezing score which showed that the difference in nasal sneezing score is much better in . control than test group. More than half of the subjects in test group (65.4%) experienced side effects from consumption of virgin coconut oil. Approximately 50% complained of gastrointestinal tract side effects. Virgin coconut oil had no significance effects as adjunct therapy in allergic rhinitis and has more side effects. We concluded that virgin coconut oil is not suitable as an adjunct therapy in allergic rhinitis.